Chair time saving method for treatment of an impacted maxillary central incisor with 15-month follow-up - Saeed Noorollahian; Farinaz Shirban (Wolters Kluwer Medknow Publications, 2018)
Maxillary permanent incisors have a major role in facial esthetics. Impaction of them has great adverse effect on smile and causes serious concerns in patient and parents. Physical barriers (e.g., overretained primary teeth, supernumerary teeth, and pathologic lesions), space problems, developmental abnormalities, altered eruption sequence, trauma, palatal clefts, and genetics can act as etiologic factors. Currently, the conventional technique to treatment of impacted teeth consists of a combined orthodontic and surgical approach, to guide the impacted teeth in a constant position and surrounded by normal hard and soft tissues. Treatment is challenging because of some limitations such as patient's age, cooperation, anchorage, and mechanotherapy possibilities. Hence, sophisticated treatment planning is crucial. A 9-year-old girl with horizontally impacted maxillary left central incisor treated with surgical exposure and closed orthodontic forced eruption with 2 × 4 partial setup fixed appliances. Force was applied with 0.014 inch nickel-titanium wire as elastic overlay and handmade ligated bracket. To save chair time in each appointment, the overlay was activated by twisting of ligature wire extensions around it. After 16-month treatment, impacted incisor emerged in oral cavity, with accepted alignment and inclination. Handmade ligated bracket with ligature wire extensions is useful for the treatment of impacted teeth. Due to easy activation of overlay in this method, chair time become short in each appointment.